Clinical analysis of low flow bypass in the treatment of chronic symptomatic middle cerebral artery occlusion - SUN Yang; WANG Ben⁃lin; LI Qi; TONG Xiao⁃guang (Chinese Journal of Contemporary Neurology and Neurosurgery, 2021)
Objective To investigate the efficacy and safety of low flow bypass in the treatment of chronic symptomatic middle cerebral artery occlusion (MCAO). Methods A total of 28 patients with chronic symptomatic MCAO who were treated in Tianjin Huanhu Hospital from January 2016 to December 2019 underwent superficial temporal artery⁃middle cerebral artery (STA⁃MCA) bypass, and the prognosis of neurological function was assessed by modified Rankin Scale (mRS). DSA or CTA were reexamined to evaluate the patency of the anastomotic site of the bridging vessels, and PWI was reexamined to evaluate improvement of cerebral perfusion. Results All 28 patients underwent STA⁃MCA bypass successfully, the success rate of operation was 100%, and the patency rate of bridge vessels was 100%. The postoperative neurological function was improved compared with that before operation, and the difference was statistically significant (mRS score 1.43 ± 0.57 vs. 2.14 ± 0.36; t = 6.301, P = 0.000). Twelve months after operation, the cerebral blood flow (CBF) and cerebral blood volume (CBV) of the affected side were significantly increased, and the mean transit time (MTT) and time to peak (TTP) were significantly decreased compared with those before operation. The mean postoperative follow⁃up was (39.41 ± 9.39) months. No new ischemic events occurred, and the bridge vessels were patchy. Conclusions Low flow bypass is safe and effective in the treatment of chronic symptomatic MCAO.